Longitudinal increase in the detection rate of Mycobacterium chimaera in heater-cooler device-derived water samples. (January 2023) - Schreiber, P.W.; Zihlmann, R.; Schärer, V.; Hasse, B.; Imkamp, F.; Schulthess, B.; Sander, P.; Zingg, W.
Summary: Background: Colonization with Mycobacterium chimaera and other non-tuberculous mycobacteria (NTM) has been reported for heater-cooler devices (HCDs) produced by several manufacturers. Up until now, exclusively LivaNova (London, UK) HCDs have been associated with M. chimaera infections after cardiac surgery. The vast majority of studies on HCD colonization were cross-sectional. Aim: We were interested in longitudinal dynamics of mycobacterial growth in HCD water samples and analysed data of a prospective mycobacterial surveillance of five LivaNova 3T HCDs. Methods: Five LivaNova HCDs were subjected to prospective mycobacterial surveillance. For each HCD and the total of HCDs, results of mycobacterial detection were analyzed. Logistic regression was applied to model the association between growth of any NTM or M. chimaera and duration of HCD use. Results: Non-tuberculous mycobacteria were isolated in 319 (48.0%, 21 water samples grew more than one mycobacterial species) of a total of 665 water samples. The most frequently detected species were M. chimaera ( N = 247/319, 77.4%), Mycobacterium gordonae (46/319, 14.4%) and Mycobacterium paragordonae (34/319, 10.7%). Detection rates increased prospectively for any NTM (odds ratio (OR) per year in use: 1.60, 95% confidence interval (CI) 1.17–2.24, P <0.001) and for M. chimaera (OR per year in use: 1.67, 95% CI 1.11–2.57, P <0.01). Conclusion: Longer duration of HCD use was associated with higher detection rates for any NTM and M. chimaera, respectively.